Formulation Development and Optimization of Bioenhanced Sublingual Tablets of Rizatriptan Benzoate to Combat Migraine - Singh, Manish Kumar; Mazumder, Rupa; Padhi, Swarupanjali; Singh, Dinesh Kumar (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: The drugs belonging to BCS class III, create various challenges for the development of sublingual dosage form due to poor absorption through sublingual mucosa. The sublingual drug delivery is suitable for potent drugs only and prevents the firstpass metabolism of drugs, leading to its direct absorption into the systemic circulation. Objectives: The purpose of the present research was to formulate a fast-dissolving sublingual tablet and enhance the permeability of rizatriptan benzoate to combat acute migraine. The work is based on a comparative selection of the optimum bioenhancer among sodium laurel sulphate and sepitrap 80. Materials and Methods: The bioenhanced sublingual tablet of rizatriptan benzoate was prepared by wet granulation technique using fluidized bed processor (FBP) equipment. A 23 full factorial design was followed for the optimization of the process, by varying three independent factors at two levels and studying their effects on three dependent variables. The Design-Expert software version 10 was used to carry out the design of experiment (DoE) trials. The optimized formulation was subjected to stability studies for 3 months as per the International Conference of Harmonization (ICH) guidelines. Results: The formulation S-3, exhibited the shortest in vitro disintegration time of 9 sec; dissolution study showed 100% drug release in 10 min; the highest in vitro percent permeability of 77.28% 90 min and highest ex vivo permeation of 82.28% of the drug in 90 min, were observed as compared to that of the control formulation. The values associated with the evaluation parameters, disintegration time, dissolution, and permeability of the optimized formulation, were found to be within the accepted range as found in the stability studies. Conclusion: The use of polyplasdone XL and sepitrap 80 could be promising for developing a fast-release sublingual tablet with improved permeability and bioavailability, especially with drugs having low permeability.
Keywords: Sublingual tablets; Rizatriptan benzoate; Migraine; Wet granulation; polyplasdone XL; Sepitrap 80; Ex vivo permeability